(untitled) (Progress Annals: Journal of Progressive Research, 2023)
The article describes how to teach the theme "Cylinder, its surface and volume" using problem educational technology. In addition, in the article provides a number of suggestions and methodical recommendations for teachers on how to use pedagogical technology.